Evaluation of agroecology efforts: Impact assessment survey of pro-soil project - Singh, Sonali; Alvi, Muzna; Gupta, Shweta; Krishnan, Smitha; Maliappan, Sudarshan; Kumar, Gopal (CGIAR System Organization, 2024)
We are conducting farm-household surveys as part of the CGIAR’s Agroecology initiative. This initiative aims to develop and scale agroecological innovations with smallscale farmers in 8 low- and middle-income countries in Asia, Africa and US region. Here, agroecology is an approach to achieving sustainable agri-food systems, grounded in a set of principles that emphasize the need to work with not against nature, and to achieve social justice by co-creating knowledge, increasing farmer and multi-actor participation and agency in decision-making, while better connecting producers to consumers.